Studi Karakteristik Porositas dan Sifat Termal pada Komposit Styrofoam - ary p, bima kusuma; Gatut Rubiono; Ikhwanul Qiram (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Styrofoam food packaging waste is plastic waste that can have a negative impact on the environment. The processing of Styrofoam food packaging waste into heat-absorbing composites is rife because it is a heat insulator and porous. This study aims to determine the porosity characteristics of the thermal properties of styrofoam composites. The process of testing composite morphology using a digital camera is then analyzed using Image-J Software. Composite heating rate and thermal conductivity testing using an electric heater with a temperature of 50ºC for 20 minutes. Composites with the lowest heating rate and thermal conductivity values are produced by porous composites of 0.173 mm2 with 0.52oC/min and 13.086 W/m.K.